Bethlehem [videorecording (DVD)] - Adler, Yuval; Haleṿi, Tsaḥi; Mar'I, Shadi ([Publisher not identified], 2014)
The complex relationship between an Israeli Secret Service officer and his teenage Palestinian informant. Shuttling back and forth between conflicting points of view, the film is a raw portrayal of characters torn apart by competing loyalties and impossible moral dilemmas, giving an unparalleled glimpse into the dark and fascinating world of human intelligence.